Radial Line Slot Array (Rlsa) Antenna Design At 28 Ghz Using Air Gap Cavity Structure - Shairi, Noor Azwan; Azian Kamaruddin, Rabiatul Adawiyah; Mohd Ibrahim, Imran; Rahim, M.A.A.; Zakaria, Zahriladha; Rahman, T.A. (Penerbit Universiti, UTeM, 2017)
A radial line slot array antenna is presented and experimentally discussed for a fifth generation (5G) mobile communication system that resonates at the frequency of 28 GHz. Additionally, it is low profile, simple structure, easy to manufacture with high gain and radiation characteristics. The two models of the antenna were simulated with different cavity thickness, which are 2.5 mm and 3.2 mm. The antenna cavity consists of an FR4 hybrid with an air gap that has produced an equivalent dielectric substrate value of 1.13. The antenna has been fed by a modified dielectric coated of 50 Ω SSMA connector as a coaxial to waveguide transition. Details of the antenna model and simulation result are presented and discussed clearly in this paper. The Computer Simulation Technology Microwave Studio 2015 software has been used as a tool to assist the simulation work. The simulation result gave the return loss of -13.99 dB at 28 GHz for air gap cavity of 2.5 mm. The higher value gain of 21.70 dBi for 3.2 mm and less than -10 dB impedance with the bandwidth from 24.27 – 32 GHz is realized. The beamwidth obtained is below 15 o of E and H planes for 2.5 mm.